Pengaruh Pemasaran Media Sosial terhadap Keterlibatan Pelanggan (Survei pada Pengguna Halodoc di Indonesia) - Ramadhani, Alif Ridha; Fauzi , Mochamad Ardan; Abdullah, Muhammad Mufti; Maesaroh, Syti Sarah; Herdiana, Oding (Jurnal Teknologi Terpadu, 2023)
This study was conducted to obtain information about the magnitude of the influence of social media marketing on customer engagement. Social media marketing (X) is the independent variable, and customer engagement (Y) is the dependent variable in this study. Followers on the Halodoc Instagram account were selected to be the population in this study, and the sample was taken randomly (simple random sampling), with 120 respondents successfully obtained. The SEM method is used to analyze data with the help of IBM SPSS AMOS 21 software for Windows in the data processing. The results of data processing illustrate that there is an influence of social media marketing on customer involvement of (0.931) with a p-value (0.002) <0.05. Artificial Intelligence-Analitycs for social media is a tool for efforts to increase the competitiveness of official Instagram managers for a business against competitors owned by analyzing content optimization through various services in the form of statistics and metrics from Artificial Intelligence-Analitycs providers, which are generally website-based. The author's recommendation for Halodoc is to increase closeness with customers so that their bonds become stronger through planning content that is useful for the community and packaged attractively. Later it is hoped that there will be more user-generated content or posting word-of-mouth recommendation comments from customers to other customers.